Odpowiedź :
Odpowiedź:
a) [tex]\frac{4}{9} * \frac{3}{4} = \frac{1}{3} \\[/tex]
b) [tex]\frac{5}{8} : \frac{7}{12} = \frac{5}{8} * \frac{12}{7} = \frac{30}{28} = \frac{15}{14}[/tex]
c) [tex]\frac{7}{8} * \frac{24}{33} = \frac{21}{33} = \frac{7}{11}[/tex]
d) [tex]1\frac{1}{8} * \frac{4}{15} = \frac{9}{8} * \frac{4}{15} = \frac{9}{30} = \frac{3}{10}[/tex]
e) [tex]2\frac{3}{5} : 5 = \frac{13}{5} * \frac{1}{5} = \frac{13}{1} = 13[/tex]
f) [tex]1\frac{5}{7} : 6 = \frac{12}{7} * \frac{1}{6} = \frac{2}{7}[/tex]
g) [tex]6\frac{1}{2} : 3\frac{1}{4} = \frac{13}{2} * \frac{4}{13} = \frac{2}{1} = 2[/tex]
h) [tex]7\frac{1}{3} : 2\frac{2}{5} = \frac{22}{3} * \frac{5}{12}[/tex]
i) [tex]2 * \frac{13 * 4}{8} = 2 * \frac{52}{8} = \frac{2}{1} * \frac{52}{8} = \frac{104}{8} = \frac{26}{2} = \frac{13}{1} = 13[/tex]
j) [tex]8\frac{3}{4} * \frac{4}{7} * 3 = \frac{35}{4} * \frac{4}{7} * 3 = \frac{5}{1} * 3 = \frac{15}{1} = 15[/tex]
k) [tex]2\frac{1}{7} * 7 * 2\frac{2}{5} = \frac{15}{7} * 7 * \frac{12}{5} = \frac{105}{7} * \frac{12}{5} = \frac{252}{7} = \frac{36}{1} = 36[/tex]
l) [tex]4 * \frac{15 * 9 }{12} = 4 * \frac{135}{12} = 4 * \frac{45}{4} = \frac{180}{4} = \frac{45}{1} = 45[/tex]